The Place de la Bastille : the story of a quartier - Reader, Keith (Liverpool University Press, 2011)
Epicentre of the Revolution of 1789, erstwhile bastion of the skilled working-class and centre of radical agitation, along with Pigalle and Montmartre a focus for popular and raffish night-life in the early twentieth century, the Bastille area of Eastern Paris (also known as the Faubourg Saint-Antoine) is now an ethnically and socially mixed quartier which still bears the traces of its previous avatars. In a fascinating tour, Keith Reader charts the history and cultural geography of this unique area of Paris, from the fortress and prison that gave the area its name to the building of the largest and costliest opera house in the world.